Chemically Stable Perovskites as Cathode Materials for Solid Oxide Fuel Cells: La‐Doped Ba0.5Sr0.5Co0.8Fe0.2O3−δ. Issue 6 (15th April 2014) - Kim, Junyoung; Choi, Sihyuk; Jun, Areum; Jeong, Hu Young; Shin, Jeeyoung; Kim, Guntae
Abstract Ba0.5Sr0.5Co0.8Fe0.2O3−δ (BSCF) has won tremendous attention as a cathode material for intermediate‐temperature solid‐oxide fuel cells (IT‐SOFC) on the basis of its fast oxygen‐ion transport properties. Nevertheless, wide application of BSCF is impeded by its phase instabilities at intermediate temperature. Here we report on a chemically stable SOFC cathode material, La0.5Ba0.25Sr0.25Co0.8Fe0.2O3−δ (LBSCF), prepared by strategic approaches using the Goldschmidt tolerance factor. The tolerance factors of LBSCF and BSCF indicate that the structure of the former has a smaller deformation of cubic symmetry than that of the latter. The electrical property and electrochemical performance of LBSCF are improved compared with those of BSCF. LBSCF also shows excellent chemical stability under air, a CO2‐containg atmosphere, and low oxygen partial pressure while BSCF decomposed under the same conditions. Together with this excellent stability, LBSCF shows a power density of 0.81 W cm−2 after 100 h, whereas 25 % degradation for BSCF is observed after 100 h.